Observation of Stark Shift of ErP/InP Single Quantum Well by Erbium Delta-Doping on InP - Pecharapa, W.; Nukeaw, J. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
A Stark shift due to external applied electric field of ErP/InP single quantum well caused by Erbium delta-doping technique on InP was firstly observed using photocurrent spectroscopy (PC). PC spectra clearly exhibited the interband transition energies of the well on a doped sample. When applying external biased voltage, Its spectra showed significant Stark shift with increasing voltage. Keywords: quantum well devices Corresponding author: E-mail: cast@kmitl.ac.th